List of fungus gnats (Diptera: Bolitophilidae, Diadocidiidae, Ditomyiidae, Keroplatidae and Mycetophilidae) of the Republic of Mordovia (Russia) - Mikhail N. Esin; Dmitriy I. Gavryushin; Alexander B. Ruchin (Acta Biologica Sibirica)
The annotated checklist includes 309 species from the families Bolitophilidae, Diadocidiidae, Ditomyiidae, Keroplatidae, and Mycetophilidae. In addition to the previous records, 242 species have been recorded for the fauna of the Republic of Mordovia for the first time. Among these are species new to Russia (Orfelia boreoalpina, Mycetophila rudis, Neoclastobasis draskovitsae, Novakia scatopsiformis) and a species new to the Palearctic (Sciophila emarginata). The collection sites are described. For the first time, 242 species are recorded for the fauna of the Republic of Mordovia. Over the course of the study, 275 species were noted in the Mordovia Nature Reserve, 91 species in National Park "Smolny", and 47 species in other locations within the region. Data on trapping methods for the collected fungus gnats are provided. Comparative data on species abundance in neighboring regions are also discussed.